2003
DOI: 10.1126/science.1078417
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Advantage of Haploidy in Large Yeast Populations

Abstract: Although seed plants and multicellular animals are predominantly diploid, the prominence of diploidy varies greatly among eukaryote life cycles, and no general evolutionary advantage of diploidy has been demonstrated. By doubling the copy number of each gene, diploidy may increase the rate at which adaptive mutations are produced. However, models suggest that this does not necessarily accelerate adaptation by diploid populations. We tested model predictions regarding rates of adaptation using asexual yeast pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 11 publications
11
114
2
1
Order By: Relevance
“…Accordingly, we might expect to observe faster-X evolution, provided that new beneficial mutations are, on average, at least partially recessive. There is little relevant information on the levels of dominance of beneficial mutations, although indirect evidence from the genetics of species differences in highly selfing taxa of plants (Charlesworth, 1992), and from comparisons of rates of adaptive evolution of haploid and diploid laboratory populations of yeast (Zeyl et al, 2003 ;Anderson et al, 2004), is consistent with a predominance of at least partial recessivity of new, selectively favourable mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we might expect to observe faster-X evolution, provided that new beneficial mutations are, on average, at least partially recessive. There is little relevant information on the levels of dominance of beneficial mutations, although indirect evidence from the genetics of species differences in highly selfing taxa of plants (Charlesworth, 1992), and from comparisons of rates of adaptive evolution of haploid and diploid laboratory populations of yeast (Zeyl et al, 2003 ;Anderson et al, 2004), is consistent with a predominance of at least partial recessivity of new, selectively favourable mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the question being asked, batch culture with serial dilution can be a simple and scalable solution (e.g., Zeyl et al 2003;Lang et al 2011). However, such cultures are only rarely propagated in a relatively constant environment and growth rate regime because doing so can require a heroic sampling regimen where back dilution is performed multiple times per day (e.g., Torres et al 2010).…”
Section: Batch Culturementioning
confidence: 99%
“…In yeast, the question was addressed concerning whether haploidy or diploidy confers an evolutionary advantage (Zeyl, Vanderford et al 2003;Zeyl 2004). Conventional wisdom suggested that having an extra gene copy would prevent harmful mutations from accumulating in the genome whereas in haploid species, harmful mutations would be detrimental to the organism.…”
Section: Sexuality In Fungimentioning
confidence: 99%